2021
DOI: 10.3390/f12101380
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography (EEG)-Based Neural Emotional Response to the Vegetation Density and Integrated Sound Environment in a Green Space

Abstract: Emotion plays an important role in physical and mental health. Green space is an environment conducive to physical and mental recovery and influences human emotions through visual and auditory stimulation. Both the visual environment and sound environment of a green space are important factors affecting its quality. Most of the previous relevant studies have focused solely on the visual or sound environment of green spaces and its impacts. This study focused on the combination of vegetation density (VD) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 63 publications
(83 reference statements)
1
9
0
Order By: Relevance
“…However, there was a significant reduction in the Focus of NE ( Figure 3 C), while there was no difference in it for CIE. We know one important theory, namely, Attention Restoration Theory (ART) [ 46 , 47 , 48 ]. In green spaces, the walking group had lower “Focus” than the sitting group [ 36 ]. The walking group’s directional attention was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was a significant reduction in the Focus of NE ( Figure 3 C), while there was no difference in it for CIE. We know one important theory, namely, Attention Restoration Theory (ART) [ 46 , 47 , 48 ]. In green spaces, the walking group had lower “Focus” than the sitting group [ 36 ]. The walking group’s directional attention was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalography (EEG), which records electrical activity inside the brain, is commonly used in research and clinical settings. It has been widely used to reflect the neural emotions of the human brain [ 32 , 33 , 34 , 35 ], and different neural emotional indicators (engagement, excitation, focus, meditation, frustration, interest, relaxation and stress) can be output through an EEG device [ 36 , 37 ]. Because emotional indicators are relatively objective compared with nonphysical cues, EEG is reliable for emotional recognition [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…A relatively stable and coherent green landscape also promotes attention recovery [9].Although the focus of this study is not biodiversity, the addition of natural elements from a green curtain wall to an urban scenic forest clearly enhances biodiversity. Moreover, a higher level of density is more likely to evoke excitatory nervous emotions [29].The laboratory conducts a relatively continuous green immersion test. The main effect analysis shows that the main effect of time is significant, indicating that the subjects' attention and arousal levels increase over time.…”
Section: Time Effect On Physiological Restorative Effectsmentioning
confidence: 99%
“…Therefore, the Rab index and some α wave channels increased significantly. Although a stable and coherent environment is conducive to attention recovery and relaxation [9], and facilitates concentrated emotional expression [29], the lack of spatial communication in sedentary groups may lead to boredom and hinder relaxation. We observed a significant time main effect of θ waves.…”
Section: Time Effect On Physiological Restorative Effectsmentioning
confidence: 99%
“…They found that focus value decreased in normal elderly participants, while engagement and interest values increased in elderly people with cognitive impairment. Zeng et al ( 47 ) found that vegetation density (VD) and integrated sound environment (ISE) had significant effects on the neuro-emotions of college students, with higher VD likely leading to the expression of excitatory neuro-emotions. In the study by Neale et al ( 44 ) used five neuro-emotional parameters provided by EEG to compare the walking status of the elderly in three different urban environments, and they found that compared with the busy and quiet urban environment, walking in urban green spaces has higher levels of “engagement” and better restorative effects in the elderly.…”
Section: Introductionmentioning
confidence: 99%